Facts about Fiber - Jennifer Hillan; R. Elaine Turner; Wendy J. Dahl (EDIS)
Fiber is a carbohydrate that we cannot digest, found in fruits, vegetables, grains, and beans. Adequate fiber intake can help us maintain good health. This revised 2-page fact sheet answers basic questions about fiber. Written by Jennifer Hillan, R. Elaine Turner, and Wendy J. Dahl. Published by the UF Department of Family Youth and Community Sciences, January 2011.